Ray Tracing of Whistler Mode Waves in Jupiter's Magnetosphere - Ning Kang; Qianli Ma; Jacob Bortnik; Murong Qin; Wen Li (Geophysical Research Letters)
Abstract Previous statistical studies have described the distributions and properties of whistler‐mode waves in Jupiter's magnetosphere, but explaining these wave distributions requires modeling wave propagation from their generation near the magnetic equator. In this letter, we conduct ray tracing of whistler‐mode waves based on realistic Jovian magnetic field and density models. The ray tracing results generally agree with the statistical wave distributions based on Juno measurements. The modeled ray paths show that high‐frequency waves generated near the equator are confined within 20° magnetic latitude due to Landau damping, low‐frequency waves can propagate to higher latitudes and lower M‐shells, with changing wave normal angles, and a portion of low‐frequency waves could propagate to high M shells at high latitudes. Our modeling results provide a theoretical interpretation of whistler‐mode wave distributions and properties, providing essential insights for future radiation belt models at Jupiter.